Novel optical and magnetic properties of Li-doped quasi-2D manganate Ca3Mn2O7 particles. Issue 28 (7th July 2017) - Zhang, Xiongnan; Liu, Weifang; Han, Yuling; Huang, Cong; Wu, Ping; Zhou, Wei; Gao, Ju; Rao, Guanghui; Wang, Shouyu
Abstract : Ruddlesden–Popper (RP) structural Li2 x Ca3−2 x Mn2 O7 ( x = 0–0.05) particles were successfully synthesized via a citrate sol–gel method. Li doping was investigated to have a positive influence on enhancing the magnetism of the system. Abstract : Ruddlesden–Popper (RP) structural Li2 x Ca3−2 x Mn2 O7 ( x = 0–0.05) particles were successfully synthesized via a citrate sol–gel method. At higher temperatures quasi-two-dimensional antiferromagnetic fluctuation effects were observed and antiferromagnetic order developed at ∼120 K, but with weak ferromagnetism. Li doping has a positive influence on enhancing the magnetism of the system. Oxygen vacancies in crystals have an important impact on the electronic properties. Interestingly, a small amount of Li substitution markedly decreases oxygen vacancies, which hence introduces disorder and leads to widening of the band gap. The obtained value of the band gap from UV-vis measurements is ∼2.88 eV which is much larger than the previous theory calculation. To appropriately correct the band gap, a more reliable method of the hybrid functional was used to investigate the electronic properties and structure of Ca3 Mn2 O7, which gave a more approximate value.